2014
DOI: 10.1590/0102-311x00027113
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking among psychiatric patients in Brazil

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
2
17
1
1
Order By: Relevance
“…Studies in the general population have shown the association between smoking and the simultaneous use of four or more medicines 35 and also with psychotropic medicines 24 . In addition, previous studies among psychiatric patients indicate an association between current smoking and substance use disorder diagnoses, but not with ex-smokers 36 . Current smokers with substance use disorder diagnoses may be more refractory to smoking cessation and potentially in need of more adjuvant therapy.…”
Section: Tablementioning
confidence: 77%
“…Studies in the general population have shown the association between smoking and the simultaneous use of four or more medicines 35 and also with psychotropic medicines 24 . In addition, previous studies among psychiatric patients indicate an association between current smoking and substance use disorder diagnoses, but not with ex-smokers 36 . Current smokers with substance use disorder diagnoses may be more refractory to smoking cessation and potentially in need of more adjuvant therapy.…”
Section: Tablementioning
confidence: 77%
“…(15,16) Studies on tobacco use among Brazilian psychiatric populations yielded different prevalences: 21.4%, 35.6% and 52.7%, depending on the universe and mental disorder being studied. (8,17,18) High tobacco consumption affects the financial lives of people with mental disorders, since they allocate up to 30% of their monthly income on cigarettes; allocating more than 4% is already considered harmful. Difficulty in obtaining cigarettes leads some individuals with mental disorders to humiliating practices, such as stealing and smoking cigarette butts, which undermines their self-esteem and self-respect.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of tobacco-based product use among people with mental disorders was higher, compared to the general population. (8) It is worth noting that, among the 50% of psychiatric patients who smoked, only 15% were able to quit smoking, whereas of the corresponding 25% of smokers in the general population, approximately 50% successfully quit. (9) People with mental disorders seem to be more vulnerable to nicotine dependence, due to its positive effect on mood, anxiety, and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of Archives of Clinical Psychiatry has been A B already discussed by other authors 15 , stressing the essential role of this journal to the development of this area. Other journals are also important tools for the expansion of this subject, noting that some articles from public health journals usually measure spirituality/ religiosity variables, but this is not the main focus of the study 25,26 and nursing journals usually are more likely to accept articles with qualitative data 27 , which represent a great number of R/S publications.…”
Section: Discussionmentioning
confidence: 99%